Caribbean Report 16-07-1993 - Ransome, Debbie (anchor); Johnson, Andy (correspondent); Rowe, Yvette (correspondent); Reid, David (correspondent); Knight, K. D. (interviewee); Hrinnak, Donna (interviewe); Brathwaite, Nicholas (interviewee); Allen, Gary (correspondent); Allen, Ken (interviewee); Croskell, Hugh (correspondent); Brathwaite, Nicholas (interviewee) (The British Broadcasting Corporation, 1993)
K.D. Knight, Jamaica’s Minister of National Security states that according to intelligence reports - the current urban crime wave is the work of twenty gangs comprising of deportees from the US and Britain. He also outlined the administrative measures being taken to monitor the movement of these deportees – correspondent Gary Allen reports. Ken Allen, Editor of the Jamaican Gleaner newspaper - reports in an interview with Debbie Ransome on the paper’s decision to run articles about the glaring and heinous crime situation in its overseas publications. Jules Bernard Trinidad and Tobago’s Police Commissioner is fighting calls for his resignation in the public interest through the Port of Spain High Court – Andy Johnson reports. The United States administration says it’s disappointed that Caribbean leaders decided not include stipulations on Human Rights and Democracy in the CARICOM Cuba Commission Agreement. The decision to establish the Commission was taken at the Heads of Government Conference in the Bahamas. Hugh Croskell interviews Donna Hrinak – Deputy Assistant Secretary of Inter-American Affairs in the US State Department who attended the conference as an observer. However, Nicholas Brathwaite, Grenada’s Prime Minister states that it was the right approach in the context of a trading relationship. Belize Prime Minister, Manuel Esquivel wants to have Belize’s agreement with Guatemala reviewed and have the legislation suspended stating that the country has given up too much - journalist David Reid reports. The Roman Catholic Church has once again indicated its opposition towards Haiti’s President Jean Bertrand Aristide’s leadership.
1. K.D. Knight, Jamaica’s Minister of National Security states that according to intelligence reports - the current urban crime wave is the work of twenty gangs comprising of deportees from the US and Britain (00:30 - 02:08).
2. Ken Allen, Editor of the Jamaican Gleaner newspaper - reports in an interview with Debbie Ransome on the paper’s decision to run articles about the glaring and heinous crime situation in its overseas publications (02:09 -05:32).
3.Jules Bernard Trinidad and Tobago’s Police Commissioner is fighting calls for his resignation in the public interest through the Port of Spain High Court – Andy Johnson reports (05:33 – 07:23).
4.The United States administration says it’s disappointed that Caribbean leaders decided not include stipulations on Human Rights and Democracy in the CARICOM Cuba Commission Agreement (07:24 - 12:01).
Keywords: Deportees -- Jamaica.; Deportees -- Emigration and immigration.; Jamaica -- Newspapers.; Police corruption -- Trinidad and Tobago.; Caribbean Community -- Commerce -- Cuba.; Belize -- Boundaries -- Politics and government.; Catholic Church -- Haiti -- Politics and government.; Aristide, Jean-Bertrand -- Politics and government.